Niemiecko-sowieckie negocjacje w sprawie traktatu o nieagresji i neutralności z 24 kwietnia 1926 r. - Mikła, Łukasz (Acta Universitatis Lodziensis. Folia Historica, 2013)
Dating back to Rapallo treaty German-Soviet political-military cooperation was based on creating the permanent conflict between both countries and the Versailles system. It could have seemed that Locarno challenged the assumption because one of the consequences of the Rhine Pact and accompanying it agreements according to the western policy was the political isolation of the USSR as well as slackening the cooperation between Berlin and Moscow. But those predictions faced the obstacle as far as the German policy was concerned as they did not want to abandon the benefits of the alliance with Kremlin. The expression of this was the conclusion of the economic treaty between both countries on 12th October 1925 as well as the fight that was led by the German delegates in Locarno with their western partners concerning the interpretation of the article 16 Covenant of the League of Nations. However the essential and fundamental evidence to the willingness to continue the cooperation established in Rapallo was the non-aggression and neutrality treaty concluded on 24th April, 1926 also called the Treaty of Berlin. The treaty consisted of four points and two additional notes. It had been concluded for 5 years. It had guaranteed the neutrality of signatories in the case of attack of the third country on one of the sides. It had also obliged to the suppression of the aggression as well as it prohibited the participation in the enemy treaties. The essential in the note was the German obligation that its access to the League of Nations will not have a negative influence on the friendly relationships between Moscow as they will not lead to recognition the Soviet Union as an aggressor and in the event of such a possibility they will not take part in the imposed sanctions. The negations on the project lasted almost half a year and demanded many detailed findings. The main dispute concerned the entry number 2. The Soviets postulated the cancellation of the word “unprovoked” as a word formulation that is contradictory to the peace policy of both sides of the treaty. The German considered that the removal of the that formula would be received in a negative way by the western countries. They also paid attention that all the political treaties of this kind included them as well as that the crossing-out of it would mean the necessity of acknowledge the USSR as an attacked side. It was emphasized that if the word “unprovoked” remained it would not diminish the meaning of the treaty for the Soviet side. According to the content of the note, it was the German government to decide whether the Soviet Union is an aggressor in the conflict with other countries regardless of the interpretation of the League of Nations. As a solution to the dispute Gustaw Stresemann – the leader of Auswärtiges Amt – offered the introduction of the word formulation “despite the peaceful attitude”. That word formulation was accepted by Moscow and it led to the signing of the treaty together with the notes included.